2019
DOI: 10.1103/physrevfluids.4.012801
|View full text |Cite
|
Sign up to set email alerts
|

Three-wave interactions among surface gravity waves in a cylindrical container

Abstract: The motion of a container filled with fluid perturbs the free surface and may result in spilling. In practice, most of the energy is localized in the modes of lowest frequencies (the gravest modes), and sloshing can be predicted once the dynamics of these modes is known. In this Rapid Communication, we investigate the nonlinear interactions between such grave modes in a cylindrical container. We first show that energy can be transferred from modes to modes with three-wave interactions: we derive the resonance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Laboratory observations of the inverse cascade in gravity wave turbulence were limited to a narrow inertial range due to the small size of the container used (Deike et al 2011), while recent attempts have been inconclusive using a larger cylindrical basin (Campagne et al 2019a) or another type of forcing (Nazarenko & Lukaschuk 2016). Michel (2019) showed that in a cylindrical container, gravity waves may sustain three-wave resonant interactions due to confinement as a consequence of a new conserved quantity (angular pseudo-momentum). These interactions have been evidenced in a gravity wave turbulence experiment in a high-gravity environment (Cazaubiel et al 2019b).…”
Section: Large-scale Wave Turbulencementioning
confidence: 99%
“…Laboratory observations of the inverse cascade in gravity wave turbulence were limited to a narrow inertial range due to the small size of the container used (Deike et al 2011), while recent attempts have been inconclusive using a larger cylindrical basin (Campagne et al 2019a) or another type of forcing (Nazarenko & Lukaschuk 2016). Michel (2019) showed that in a cylindrical container, gravity waves may sustain three-wave resonant interactions due to confinement as a consequence of a new conserved quantity (angular pseudo-momentum). These interactions have been evidenced in a gravity wave turbulence experiment in a high-gravity environment (Cazaubiel et al 2019b).…”
Section: Large-scale Wave Turbulencementioning
confidence: 99%
“…Although forbidden by weak turbulence theory for plane gravity waves, 3-wave interactions are authorized theoretically in cylindrical containers where axisymmetric eigenmodes are important [28]. Indeed, axisymmetric modes imply a new conserved quantity (angular pseudomomentum) [28]. The large-scale axisymmetric modes being important in our study, they thus modify the type of interaction mechanism for gravity waves, and probably change the one for capillary waves.…”
mentioning
confidence: 76%
“…In the gravity regime, we find that 3-wave interactions occur (c ≈ 0, b = 0). Although forbidden by weak turbulence theory for plane gravity waves, 3-wave interactions are authorized theoretically in cylindrical containers where axisymmetric eigenmodes are important [28]. Indeed, axisymmetric modes imply a new conserved quantity (angular pseudomomentum) [28].…”
mentioning
confidence: 99%
“…For laboratory generated waves, the size and the shape of the container can also play a role. Recently, an experimental and theoretical study [33] has indeed demonstrated that in a confined cylindrical geometry the large modes of gravity surface waves interact with each other by a three-wave resonant process, whereas plane gravity waves are subjected only to the four-wave resonant interaction mechanism [32]. Here, despite the cylindrical shape of the container, the mother waves are forced as plane waves and at frequencies significantly larger than those corresponding to the first tank eigen-modes.…”
Section: Discussionmentioning
confidence: 99%